Comparative study of the plasma pharmacokinetics and tissue residues of trimethoprim in silky fowls and 817 broilers after single oral administration - HuiYu Hu; JinHua Qiu; RuoNan Li; Dong Li; QianYong Wang; QuanXi Wang; YuFang Ma; Wen Yang; Rui Xu; LingLing Liu; Yue Su; HuiHui Song; et al. (Poultry Science, 2023)
ABSTRACT: A comparative study was performed to investigate the differences in plasma pharmacokinetics (PKs) and tissue residues of trimethoprim (TMP) between silky fowls and 817 broilers. The 2 breeds of chickens received compound sulfadiazine suspension by gavage at 20 mg/kg (measured as TMP). Blood and tissue samples were collected at predetermined time points. The concentrations of TMP in plasma and tissue samples were determined by a validated high-performance liquid chromatography (HPLC) method. The plasma concentration-time data were subjected to noncompartment analysis by WinNonlin program (Pharsight Co., Mountain View, CA). The mean plasma concentrations of TMP in silky fowls were significantly lower than those in 817 broilers at all time-points. Significant differences were also observed between silky fowls and 817 broilers in maximum concentration (Cmax), area under the curve from time 0 to 24 h (AUC0 → 24 h), apparent volume of distribution (Vd), and total body clearance (ClB). Silky fowls had significantly higher muscle TMP concentrations and longer tissue residual time than 817 broilers. The tissue concentration of TMP followed the order of leg muscle > breast muscle > liver, which was obviously different from that of 817 broilers. The half-lives of TMP in the leg muscle, breast muscle, and liver of silky fowls were 31.42, 10.78, and 0.38 d, respectively. The current withdrawal time (WDT) was not sufficient to prevent violative residues of TMP in the edible tissues of silky fowls, and a WDT much longer than 8 d might be required.